(untitled) (Research, Society and Development, 2022)
Thermography in equine medicine is applied in the prevention, diagnosis and prognosis of diseases, as it can detect changes in peripheral blood flow. It can also act in the treatment by monitoring the instituted therapy. Skin infrared imaging thermometry is a method that detects, records, and produces images reflecting the microcirculatory dynamics of the skin surface in real time. The technique emerged from the studies of Hippocrates and has since gone through several advances, reaching significant milestones in the period of World War II, when it was effectively used in the tank’s night vision system. In the 1970s, there was a big leap when it was possible to generate an image in five minutes. Several scientific studies point out its functionality both in human medicine and veterinary medicine with precision and practicality. It has been applied in equine sports medicine to clinical practice to assess musculoskeletal injuries as an indicator of physiological stress, assess resistance, be part of the anti-doping program of the International Equestrian Federation. It is an easy to apply, safe, and affordable method It proves to be an excellent non-invasive diagnostic method for athlete horses.